Active fund managers and earnings management at portfolio companies. Issue 1 (27th June 2019) - Farooqi, Javeria; Jory, Surendranath; Ngo, Thanh
Abstract : Purpose: This paper aims to examine the association between the types of mutual funds, i.e. active versus passive, and the level of earnings manipulation in companies that comprise their stock portfolios. Design/methodology/approach: The authors use Cremers and Petajisto's (2009) classification of mutual funds by active share and tracking error volatility to differentiate between active and passive mutual funds. To assess the extent of earnings quality at portfolio companies, the authors measure accruals earnings management and real earnings management. Findings: The authors find that the portfolio firms held by active fund managers exhibit lower levels of earnings manipulation. The inverse relationship between earnings management and fund holdings is more pronounced at higher levels of active share selection among concentrated active fund managers. Practical implications: The degree to which earnings management influences mutual funds' investment behavior has significant implications for the stability of the US stock market. Based on the findings that earnings management at portfolio companies serves as a potential instrument to guide funds' investment decisions, future research would examine how these investment preferences exert price pressure (if any) on the stock of the portfolio companies. It would also help to ascertain whether the investment preferences of fund managers with respect to earnings management help to render the stock market more or less efficient. Originality/value: This paper contributes to the understanding of how actively managed funds perform stock selection. Earnings manipulation leads to negative earnings quality that would inhibit stock performance over time. Active fund managers, who dynamically manage their exposures to systematic and stock-specific risks (in their attempt to outperform their benchmark index), target firms that manage earnings less to form part of their investment portfolios.